2010
DOI: 10.1123/smej.4.1.1
|View full text |Cite
|
Sign up to set email alerts
|

What are we teaching our students? A descriptive examination of the current status of undergraduate sport mnagement curricula in the United States

Abstract: As undergraduate sport management programs continue to grow and expand in the United States, and with the recently developed Commission on Sport Management Accreditation (COSMA) accreditation guidelines for such programs, it is important to examine the current status of undergraduate sport management curricula in the U.S. The purpose of this study was to provide an overview of each program’s curriculum and other program components such as the school/college in which each program is housed, program name, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Shortly thereafter, the NASPE partnered with NASSM to develop an accreditation process strictly for sport management programs (Eagleman & McNary, 2010). Between 1990 and 2009, numerous sport management scholars suggested or directly recommended the necessity to have an accreditation body for sport management (c.f., Fielding et al, 1991;Mahoney et al, 2004;Zakrajsek, 1993).…”
Section: Sport Management Program Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Shortly thereafter, the NASPE partnered with NASSM to develop an accreditation process strictly for sport management programs (Eagleman & McNary, 2010). Between 1990 and 2009, numerous sport management scholars suggested or directly recommended the necessity to have an accreditation body for sport management (c.f., Fielding et al, 1991;Mahoney et al, 2004;Zakrajsek, 1993).…”
Section: Sport Management Program Assessmentmentioning
confidence: 99%
“…Scholars have previously indicated that studies regarding assessment of sport management curriculum are limited (Eagleman & McNary, 2010). Over the course of the last several decades, however, several important studies have assessed curriculum in an investigative manner.…”
Section: Curriculum Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 1990s, the great majority of sport management programs in the U.S. were housed in departments of physical education (Alsop & Fuller, 2001;Fielding, Pitts, & Miller, 1991;Sawyer, 1993). By 2010, Schools of Health, Physical Education, & Recreation (HPER) were still the most popular placement for undergraduate sport management programs with 35%, but Schools of Business had grown to 25% of programs (Eagleman & McNary, 2010).…”
mentioning
confidence: 99%